ANALISIS KANDUNGAN ZAT BERBAHAYA PADA MAKANAN MENGGUNAKAN BAHAN ALAMI (EKSTRAK BUAH NAGA DAN EKSTRAK KUNYIT) - Tri Wahyuni; Siti Alwita (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Chemicals such as formalin and borax are actually chemicals that can only be used for purposes outside the body, meaning that borax and formalin are not allowed to enter the human body because they will have a serious impact on damaging the organs inside. The purpose of this study was to determine the presence of formalin and borax in snacks at SD Swasta Tj.Anom. This research method is experimental research and then covers the entire research. This study uses turmeric and dragon fruit extracts as research materials. indicators. The results of several samples observed by researchers contain formalin, namely sausages, instant noodles. And some samples contain borax, namely sausages, meatballs and instant noodles. Based on the results of the study, it was found that there are dangers posed when consuming foods that contain a lot of borax and formalin, one of which can damage liver and kidney function and can even trigger cancer.